2006
DOI: 10.1152/ajpheart.01109.2005
|View full text |Cite
|
Sign up to set email alerts
|

NO and prostanoids blunt endothelin-mediated coronary vasoconstrictor influence in exercising swine

Abstract: Withdrawal of the endothelin (ET)-mediated vasoconstrictor influence contributes to metabolic coronary vasodilation during exercise. Because production of nitric oxide (NO) and prostanoids increases with increasing shear stress and because NO and prostanoids are able to modify the release of ET, we hypothesized that the withdrawal of ET-mediated coronary vasoconstriction during exercise is mediated through NO and/or prostanoids. To test this hypothesis, 19 chronically instrumented swine were studied at rest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 36 publications
6
70
2
Order By: Relevance
“…The withdrawal of ET-mediated coronary vasoconstriction after MI was not due to a loss of ET receptors, as coronary arterioles isolated from remote myocardium after MI displayed a more pronounced (34). The withdrawal of ET-mediated vasoconstriction during exercise in the normal heart was shown to be mediated by NO and prostanoids (37); these data indicate that recruitment of coronary flow reserve during exercise depends critically on a healthy well-functioning endothelium. Since endothelial dysfunction has been shown to be present after MI (4,47,49), we investigated in the present study if the contributions of the three main endothelial vasoactive systems (NO, prostanoids, and ET) to control of coronary resistance vessel tone in remodeled myocardium were altered at rest and/or during exercise.…”
Section: Integrated Endothelial Control Of Coronary Resistance Vesselmentioning
confidence: 79%
See 3 more Smart Citations
“…The withdrawal of ET-mediated coronary vasoconstriction after MI was not due to a loss of ET receptors, as coronary arterioles isolated from remote myocardium after MI displayed a more pronounced (34). The withdrawal of ET-mediated vasoconstriction during exercise in the normal heart was shown to be mediated by NO and prostanoids (37); these data indicate that recruitment of coronary flow reserve during exercise depends critically on a healthy well-functioning endothelium. Since endothelial dysfunction has been shown to be present after MI (4,47,49), we investigated in the present study if the contributions of the three main endothelial vasoactive systems (NO, prostanoids, and ET) to control of coronary resistance vessel tone in remodeled myocardium were altered at rest and/or during exercise.…”
Section: Integrated Endothelial Control Of Coronary Resistance Vesselmentioning
confidence: 79%
“…Since statistical analyses revealed no differences between male and female swine, data from both sexes were pooled. Data on part of the normal swine have been previously reported (37).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…NO not only induces coronary vasodilation through cGMPmediated activation of vascular smooth muscle K ϩ channels (26) but also produces vasodilation by inhibiting the coronary vasoconstrictor influence of ET during exercise (30). We recently observed that this inhibition of ET by NO, which is likely cGMP-mediated (5,14,25), occurs principally through a reduced production of ET from Big ET (7).…”
mentioning
confidence: 99%